Penerapan, kelebihan, dan kelemahan metode pembelajaran pai: ceramah, tanya jawab, ibrah mauidzah, drill, hafalan, demonstrasi, karyawisata, resitasi - Ramadani, Firman Ashar (Maliki Interdisciplinary Journal, 2026)
Islamic Religious Education (PAI) plays an important role in developing students’ cognitive, affective, and psychomotor aspects. The success of the learning process is largely determined by the selection and implementation of appropriate teaching methods by educators. This paper aims to examine the application, strengths, and weaknesses of various PAI teaching methods, including lecture, question-and-answer, ibrah mauidzah, drill, memorization, demonstration, field trips, and recitation. The study employs a library research method with a descriptive qualitative approach. The findings indicate that each method has its own characteristics, advantages, and limitations. The lecture method is effective for delivering material systematically, while the question-and-answer method enhances interaction and student participation. The ibrah mauidzah method contributes to character building, whereas drill and memorization strengthen memory retention. The demonstration method provides direct learning experiences involving psychomotor aspects, while field trips and recitation support contextual learning and student independence. There is no single method that is universally applicable; therefore, teachers are required to combine various methods creatively and innovatively in accordance with students’ characteristics and learning objectives. Thus, PAI learning is expected to become more effective, engaging, and meaningful.